2019
DOI: 10.1038/s41436-018-0287-y
|View full text |Cite
|
Sign up to set email alerts
|

ATG7 and ATG9A loss-of-function variants trigger autophagy impairment and ovarian failure

Abstract: Our results unveil that impaired autophagy is a novel pathophysiological mechanism involved in human POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 36 publications
4
30
0
1
Order By: Relevance
“…In keeping with this, all reported lists have a varied capture of POI genes, and there has been only a modest success using panels for the genetic analysis of patients with POI. Recognizing the shortcomings of stringent criteria for analysis, WES data from published POI cohorts have been reanalyzed to identify previously missed diagnoses in KHDRBS1 , ATG7 , and ATG9A (Delcour et al, ; Wang et al, ). Our gene list contained 482 genes which had a predicted role in POI based on known variants in human cases, relevant phenotypes in mice with gene disruption, genetic associations in POI cohorts, and/or in vitro studies (File S1).…”
Section: Variants Of Interestmentioning
confidence: 99%
“…In keeping with this, all reported lists have a varied capture of POI genes, and there has been only a modest success using panels for the genetic analysis of patients with POI. Recognizing the shortcomings of stringent criteria for analysis, WES data from published POI cohorts have been reanalyzed to identify previously missed diagnoses in KHDRBS1 , ATG7 , and ATG9A (Delcour et al, ; Wang et al, ). Our gene list contained 482 genes which had a predicted role in POI based on known variants in human cases, relevant phenotypes in mice with gene disruption, genetic associations in POI cohorts, and/or in vitro studies (File S1).…”
Section: Variants Of Interestmentioning
confidence: 99%
“…Indeed, although using specific tools (e.g., SIFT, Polyphen2) for filtering variants is an efficient method for proposing candidates from large amounts of data, they have been related to false negative results. We have used this methodology in two previous studies, one of which led a first description of functional mutations in ATG (autophagy) genes leading to POI (Carlosama et al., , Delcour et al., ).…”
mentioning
confidence: 99%
“…Several studies have suggested the involvement of the autophagy process in the regulation of the ovarian reserve of primordial follicles. For example, autophagy is implicated in maintaining the primordial oocyte pool in murine newborns [11], and the induction of autophagy at birth seems to be a crucial step to preserve the stock of primordial follicles [12,13].…”
Section: Follicular Ovarian Reserve and Its Regulationmentioning
confidence: 99%